Technological Factors and Student-to-Student Connected Classroom Climate in Cloud Classrooms. (October 2018) - MacLeod, Jason; Yang, Harrison Hao; Zhu, Sha; Shi, Yinghui
In an effort to address student engagement challenges, much research has explored student-to-student connected classroom climate (CCC). Research positively associates CCC to the benefits of student integration, learning, and retention in face-to-face environments. However, few studies have examined CCC in computer-mediated environments. This study provides empirical evidence of the relationships between key technological factors and CCC in cloud classrooms. A survey was administered to 641 college students, and the results indicate that four of the five technological factors examined were positively associated with CCC: advanced computer self-efficacy, program/software computer experience, Internet/entertainment computer experience, and computer importance. Basic computer self-efficacy was not related to CCC. These findings identify mechanisms that can improve CCC in cloud classrooms. Researchers and practitioners should use this knowledge to develop, implement, and assess the cloud classroom. In addition, this study contributes knowledge that can direct student training of digital literacies for improving the learning processes of cloud classrooms in higher education.